Experiences of Neophyte Barangay Councilors: A Phenomenological Study - Sebrero, Dirb Boy O.; Relacion, April Farell M. (Future Science / FSH-PH Publications, 2025)
Effective leadership at the barangay level is essential for responsive and inclusive local governance, yet neophyte barangay councilors often face a steep learning curve as they transition into public service roles. This study explored the experiences of neophyte barangay councilors in a municipality in Zamboanga del Sur. It utilized a qualitative approach and followed a phenomenological research design, employing a semi-structured interview guide in conducting in-depth interview with seven neophyte barangay councilors as participants of this study. Data were analyzed using Moustakas’ thematic analysis method. Moustakas thematic analysis is a method used to explore and interpret the lived experiences of individuals to uncover the essence of a phenomenon. This study identified four themes: bridging idealism with reality facing the challenging yet fulfilling journey of new barangay councilors, navigating leadership with limited preparation, support, and resources, and harnessing collective wisdom and collaborative network for effective leadership. The findings further reveal that newly elected officials often enter office with enthusiasm and idealism but are quickly confronted with the complexities of local governance resulting in uncertainty, administrative difficulties, and diminished confidence, especially in handling technical tasks such as drafting ordinances. It is recommended that the Department of Interior and Local Government may develop a training program targeted at neophyte barangay officials with practical workshops on legislative drafting, and project planning, as well as simulations on handling real-life governance issues.